Exploring teachers’ experience with student character development : a comparative analysis - Nik Md Saiful Azizi Nik Abdullah,; Alwi Lubis,; Rabi’atul Athirah Muhammad Isa, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The purpose of this qualitative research is to explore teachers’ perceptions in inculcating moral values to develop student character, to identify different challenges faced by teachers and to discover how teachers overcome their challenges in both Islamic as well as conventional schools. Purposive sampling and semi-structured interviews were used to obtain more in-depth information from six participants, and a thematic approach was used to analyse the data. Findings reveal the teachers’ perception of developing student character, the challenges and how they overcome these challenges to develop students’ character. A noticeable difference noted is that teachers in conventional schools face challenges due to the limitations of teachers’ rights. Other challenges faced by teachers in both types of school include family background, school environment, peer pressure, and social media. The implication of this study is to raise awareness among educators and higher authorities as well as parents, about the challenges teachers face in Islamic schools and conventional schools in developing student character. This helps in correcting the misconception that teachers are solely responsible for promoting good moral character in their students.